Systematic Literature Review Study: ESG, Profitability, Capital Structure, and Firm Value - Borahima, Fatimah Rahman; Djaddang, Syahril (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study aims to examine the influence of Environmental, Social, and Governance (ESG), profitability, and capital structure on firm value using a Systematic Literature Review (SLR) approach. A total of 36 national and international journal articles published between 2019 and 2025 were analyzed using the PRISMA framework. The findings indicate that ESG disclosure and profitability (ROA/ROE) generally have a positive impact on firm value. However, the effect of capital structure (DER) tends to vary depending on industry sector and financial strategy. The study also identifies research gaps, including the limited use of ESG as a moderating variable, lack of cross-industry studies, and minimal application of advanced quantitative methods. These findings are expected to serve as a conceptual foundation for future research.